2021
DOI: 10.3390/su131910675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement of PCM Melting in Double Tube Heat Exchangers Using Different Combinations of Nanoparticles and PCM (The Case of Renewable Energy Systems)

Abstract: In this work, the melting process of phase change material (PCM) in double tube heat exchangers was investigated and evaluated through the use of different combinations (1, 2, 3% Nano-Enhanced PCM and 1, 3, 5% Nano-HTF) of GQD, as well as SWCNT nanoparticles and PCM (RT82). In this study, the effect of three different methods, namely the dispersion of nanoparticles in PCM (nano-enhanced PCM), the dispersion of nanoparticles in HTF (nano-HTF), and the simultaneous dispersion of nanoparticles in PCM and HTF (nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…18 So, the length of fin, fin density, and fin angle are the main effects on PCM HE, in addition to the shape and orientation of PCM HE, these parameters can enhance the melting process but reduce solidification performance and vice versa. 19 The uniform five longitudinal fins used as a reference model that greatly enhances heat performance compared with nonfin HE. Nonetheless, they have a negative effect in terms of showing unequal melting and solidification below and above the tube, the length of the fins should be modified to get the best or optimal heat performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 So, the length of fin, fin density, and fin angle are the main effects on PCM HE, in addition to the shape and orientation of PCM HE, these parameters can enhance the melting process but reduce solidification performance and vice versa. 19 The uniform five longitudinal fins used as a reference model that greatly enhances heat performance compared with nonfin HE. Nonetheless, they have a negative effect in terms of showing unequal melting and solidification below and above the tube, the length of the fins should be modified to get the best or optimal heat performance.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of PCM HE has a great effect on PCM HE's understanding of melting and solidification processes 18 . So, the length of fin, fin density, and fin angle are the main effects on PCM HE, in addition to the shape and orientation of PCM HE, these parameters can enhance the melting process but reduce solidification performance and vice versa 19 …”
Section: Introductionmentioning
confidence: 99%
“…has a great effect on PCM H.E., the full understand of melting and solidification processes, where the natural convection is dominated mode of heat transfer, that depend in density change, and this natural convection up stream can restricted or enhance by geometry of container (Huang, Yang et al 2022). So, the length of fin, fin density and fin angle are the main effects on PCM H.E., in addition of shape and orientation of PCM H.E., these parameters can enhance melting process but reduce solidification performance and vice versa (Motevali, Hasandust Rostami et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [176]- [185], [186]- [189] have tested numerically and experimentally double-pipe LHTES systems. A double tube LHTES with RT82 as PCM with the dispersion of graphene quantum dot and single-walled carbon nanotubes were studied numerically with Ansys Fluent [176]. The results indicated that reducing pipe and fin thickness by 0.5mm (from 1.5 mm to 1mm) reduced the melting rate by 31% [176].…”
Section: Numerical and Experimental Studies Of Double-pipe Lhtes Systemsmentioning
confidence: 99%
“…A double tube LHTES with RT82 as PCM with the dispersion of graphene quantum dot and single-walled carbon nanotubes were studied numerically with Ansys Fluent [176]. The results indicated that reducing pipe and fin thickness by 0.5mm (from 1.5 mm to 1mm) reduced the melting rate by 31% [176]. A concentric double tube containing Al2O3 nanofluid and n-eicosane was studied experimentally, and the results indicated that the average heat transfer effectiveness was increased with an increased flow ratio [177].…”
Section: Numerical and Experimental Studies Of Double-pipe Lhtes Systemsmentioning
confidence: 99%